Sequence Variants in BMPR2 and Genes Involved in the Serotonin and Nitric Oxide Pathways in Idiopathic Pulmonary Arterial Hypertension and Chronic Thromboembolic Pulmonary Hypertension: Relation to Clinical Parameters and Comparison with Left Heart Disease - Ulrich Somaini, Silvia; Szamalek-Hoegel, Justyna; Hersberger, Martin; Fischler, Manuel; Garcia, Jesus Solera; Huber, Lars C.; Grünig, Ekkehard; Janssen, Bart; Speich, Rudolf (Respiration, 2010)
Background: Idiopathic pulmonary arterial hypertension (IPAH) and chronic thromboembolic pulmonary hypertension (CTEPH) share important pathogenic and clinical features. BMPR2 mutations are important in the pathogenesis of IPAH, but little is known about the genetic background in CTEPH. Objective: To search for mutations and polymorphisms in genes involved in the BMPR2, serotonin and nitric oxide pathways possibly associated with pulmonary and cardiac disorders in IPAH and CTEPH. Methods: In a cohort of Swiss patients with IPAH (n = 16) and CTEPH (n = 16), and in 24 controls with left heart disease without PH, polymorphisms in the BMPR2, 5-HHT, 5-HTR-2A and eNOS genes were analyzed and correlated with various clinical, functional and hemodynamic parameters. Results: We found a BMPR2 missense mutation in a patient with coronary artery disease (CAD) without PH but no BMPR2 mutations in our collective with late-onset sporadic PH. In patients with polymorphic variants of the BMPR2 gene, the number of blood platelets and oxygen saturation were increased. The c.600A→C synonymous variant was associated with worse exercise capacity and decreased quality of life in PH. We found no significant differences for any measured parameter according to the eNOS, 5-HTR2A and the 5-HTT polymorphisms, although there was a higher allelic frequency of the 5-HTT long variant in IPAH than in CTEPH and controls. Conclusion: Our first report of a BMPR2 mutation in a patient with CAD without PH is interesting and warrants further investigation. Our study may reflect the clinical status and genetic background in a typical PH cohort as seen in a single tertiary care referral center.